Development and evaluation of low-cost walker with trunk support for senior citizen - Paloma Hohmann Poier (Revista da Escola de Enfermagem da USP, 2017)
Objective: Develop and evaluate a low-cost walker with trunk support for senior citizens. Method: Two-stage descriptive study: development of a walker with trunk support and evaluation with fourth age senior citizens. Results: Twenty-three fourth age senior citizens were selected. The evaluated criteria were the immediate influence of the walker on the static stabilometry with baropodometer and the evaluation of gait with accelerometers monitoring time and amplitude of the hip movement. There was a significant decrease in the body oscillation of senior citizens with the use of the developed walker, and there were changes in the joint amplitudes of the hip, but they were not significant. Conclusion: Using low-cost materials, it was possible to develop and equipment that met resistance and effectiveness requirements. The walker interfered in the balance of the senior citizens, reducing significantly the static body oscillation.